Fabrication and Characteristics of Methyl-Modified TiO2-SiO2 Membrane by Sol-Gel Method: Effect of Titania Content. Issue 1 (2nd September 2021) - Yang, Jing; Zhang, Gaofei; Zhang, Ruifeng; Guo, Yingming; Li, Bo
Abstract: Titania-doped methyl-modified silica membrane was prepared via an acid-catalyzed sol-gel method using tetraethylorthosilicate and methyltriethoxysilane as the silicon source and tetraethylorthosilicate as the titanium source. The influence of titanium/silicon molar ratio ( nTi ) on the properties of TiO2 -SiO2 sol and microstructure of unsupported TiO2 -SiO2 membrane was systematically studied. The gas permeance and vapor stability of TiO2 -SiO2 membrane were also tested. The results showed that, as nTi increased, the density, viscosity, refractive index and viscous activation Gibbs free energy of TiO2 -SiO2 sol gradually decreased, while the particle size increased. The existence of Si-CH3 and Ti-O-Si bonds in TiO2 -SiO2 membrane proved that the hydrophobic modification was successful and that SiO2 was chemically bonded to TiO2, respectively. The titanium element exists in form of Ti-O-Si structure and anatase phase TiO2 in TiO2 -SiO2 membrane. When operated at 150 °C and a pressure difference of 0.3 MPa, the H2 permeance and H2 /CO2 permselectivity of TiO2 -SiO2 membrane with nTi =0.1 is 6.84 × 10 −6 mol· m −2 ·Pa −1 · s −1 and 6.96, respectively. After aging in the moist circumstance for 9 d, the H2 permeance of TiO2 -SiO2 membrane reduced by 6.86%, while the H2 /CO2 permselectivity increased by 2.71%.